2018
DOI: 10.1016/j.jclepro.2018.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Production of saccharides from sugar beet pulp by ultrafast hydrolysis in supercritical water

Abstract: 10Sugar beet pulp (SBP) is the major by-product in sugar industry. To make profit out of this 11 undervalued residue, the FASTSUGARS process was proposed as a solution, combining 12 the advantages of supercritical water as hydrolysis medium with very short reaction times 13 in the so-called ultrafast reactors. Operating at 390 ºC, 25 MPa and reaction times between 14 0.11 and 1.15 s it was possible to convert SBP into sugars and to obtain a lignin-like solid 15 fraction. The highest yields of C-6 and C-5 sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…If visualizing the hydrolysis of an individual biomass particle, it makes 255 reaction time or more severe reaction conditions) to get hydrolyzed to the same extent 257 than a particle half its size. Therefore, following the same reasoning already observed 258 when comparing sbp to wb results [17], initial particle size was acting as a mass transfer 259 resistance, so that under same reaction time and operating conditions, bigger particle 260 size produced lower conversion. 261…”
Section: 3pilot Plant Performance Compared To Laboratory Plant Permentioning
confidence: 59%
See 3 more Smart Citations
“…If visualizing the hydrolysis of an individual biomass particle, it makes 255 reaction time or more severe reaction conditions) to get hydrolyzed to the same extent 257 than a particle half its size. Therefore, following the same reasoning already observed 258 when comparing sbp to wb results [17], initial particle size was acting as a mass transfer 259 resistance, so that under same reaction time and operating conditions, bigger particle 260 size produced lower conversion. 261…”
Section: 3pilot Plant Performance Compared To Laboratory Plant Permentioning
confidence: 59%
“…To evaluate 118 this scaling up sugar beet pulp (SBP) and wheat bran (WB) were hydrolyzed in the 119 FASTSUGARS pilot plant and results were compared to previous ones obtained in the 120 laboratory scale plant [9,17]. 121…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining solids after hydrolysis consisted of 85 wt.% lignin, with about 5 wt.% glucans still remaining in the hydrolysis residue. Martínez et al (2018) studied the implementation of supercritical water for hydrolysis of beet pulp at 390 • C and 250 bar, varying the reaction times between 0.11 and 1.15 s. The highest C 6 and C 5 yields of 61 and 71 wt.% were obtained at 0.11 s, respectively, and the use of short reaction times produced low concentrations of dehydration byproducts. Also, Martínez et al (2019) compared the supercritical hydrolysis of sugar beet pulp and wheat bran at laboratorial and pilot scale and concluded that long hydrolysis times were detrimental to the obtainment of high sugar yields, however, in pilot scale tests, the use of higher average particle sizes reduced sugars degradation, leading to sugar yields up to 90% of the theoretical maximum.…”
Section: Supercritical Watermentioning
confidence: 99%